Tuberculosis and nutrition: disease perceptions and health seeking behavior of household contacts in the Peruvian Amazon - Baldwin, M. R. (2004)
SETTING: Households of TB patients in the Peruvian Amazon. OBJECTIVE: To investigate how knowledge and beliefs of household contacts about TB affected health seeking behavior. DESIGN: Interviews with 73 patients finishing treatment and 79 of their adult household contacts. RESULTS: Contacts were knowledgeable about free screening and treatment, but contacts who noted weight loss, not cough, were more likely to be screened for TB (P = 0.03). Forty-two per cent reported that TB was prevented by nutrition, 28% by separating eating utensils, and only 19% by avoiding a coughing patient. Only one household contact reported being stigmatized. Stigma centered upon nutrition, and only 12% knew of the association between TB and HIV. Only 14% had a BMI <20, yet 30% reported regularly going to sleep hungry. Free food packages were reported to be the most important reason for treatment adherence by 33% of patients. CONCLUSION: Contacts misperceived TB as a nutritional disease and did not fear airborne transmission, which should be corrected by public health education. Weight loss, and not cough, led to screening. Stigma appeared to be minimized because risk was perceived as personal, through malnutrition, rather than exposure-based. Nutritional incentives that utilize these beliefs may reduce diagnostic delay and enhance treatment adherence.